Policy Analysis of the SRIKANDI Archiving System in Banten Province - Naufal, Dody; Aryono, Gagah Dwiki Putra (Jurnal Ilmu Administrasi Negara (JUAN), 2025)
In the digital transformation era, the effective management of government archives is essential for ensuring administrative efficiency, transparency, and data security. The traditional manual archiving systems present significant limitations, including difficulty in document retrieval, risk of data loss, and inefficiencies in storage and management. To address these issues, the Indonesian government has implemented the SRIKANDI (Integrated Dynamic Archival Information System) application, which aims to provide a comprehensive, digital approach to document management. This study analyzes the implementation of the SRIKANDI system within the Department of Communication, Informatics, Statistics, and Encryption of Banten Province, focusing on its effectiveness, challenges, and policy implications. Employing a qualitative research design, the study utilized Thematic Analysis as its primary method, gathering data through interviews, direct observation, and document reviews. The research identified key themes including improved efficiency in archival digitization, enhanced document security and accessibility, integration and interoperability challenges, and the critical need for technical training. Findings indicate that while SRIKANDI has substantially improved document retrieval, reduced the risk of data loss, and promoted accountability through digital traceability, its implementation is hindered by inadequate infrastructure, insufficient user training, and limited system integration. Many users lack the digital literacy necessary to fully utilize the system, resulting in underuse of advanced features. Moreover, compatibility issues with existing systems lead to redundant data entry and inconsistencies. In conclusion, while SRIKANDI presents significant benefits in modernizing archival practices, its success depends on comprehensive training, improved infrastructure, and strengthened cross-agency interoperability to create a more unified and efficient digital government ecosystem.